2006
DOI: 10.1097/01.mcd.0000181605.55382.9a
|View full text |Cite
|
Sign up to set email alerts
|

Supernumerary marker chromosome 7 and maternal uniparental disomy 7 in a boy with growth retardation and triangular face

Abstract: We report on a 12-month-old boy with pre and post-natal growth retardation, triangular face and mild psychomotor retardation. Karyotyping revealed a supernumerary marker chromosome (SMC) in 36% of cells. Using fluorescence in situ hybridization and BAC clones, the supernumerary marker chromosome was found to be a highly deleted chromosome 7 with breakpoints within the pericentric euchromatin (partial trisomy 7). Microsatellite typing indicated maternal uniparental disomy of chromosome 7 (matUPD7). The patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…These cases include a father and son [Blennow et al, 1993, 1994; Anderlid et al, 2001], a mother and two children [Tan‐Sindhunata et al, 2000] and five de novo patients [Velagaleti et al, 2002; Daniel and Malafiej, 2003; Chantot‐Bastaraud et al, 2004; Lichtenbelt et al, 2005]. In our comparison, two cases with SMC(7) and having maternal UPD (uniparental disomy) [Miyoshi et al, 1999; Eggermann et al, 2006] were excluded, since they presented with the Silver–Russell syndrome (SRS) phenotype. Unfortunately, UPD has not been tested in all patients of Table I; however, the absence of SRS traits in the five patients (C, D, F, G, J), where this molecular analysis has not been performed, suggests a biparental inheritance of the two normal chromosomes 7.…”
Section: To the Editormentioning
confidence: 81%
“…These cases include a father and son [Blennow et al, 1993, 1994; Anderlid et al, 2001], a mother and two children [Tan‐Sindhunata et al, 2000] and five de novo patients [Velagaleti et al, 2002; Daniel and Malafiej, 2003; Chantot‐Bastaraud et al, 2004; Lichtenbelt et al, 2005]. In our comparison, two cases with SMC(7) and having maternal UPD (uniparental disomy) [Miyoshi et al, 1999; Eggermann et al, 2006] were excluded, since they presented with the Silver–Russell syndrome (SRS) phenotype. Unfortunately, UPD has not been tested in all patients of Table I; however, the absence of SRS traits in the five patients (C, D, F, G, J), where this molecular analysis has not been performed, suggests a biparental inheritance of the two normal chromosomes 7.…”
Section: To the Editormentioning
confidence: 81%
“…The facts that the derivative chromosome 1 carried euchromatic material and that maternal UPD 1 per se is without a phenotype,154 makes UPD unlikely to be causative for the clinical findings. A case of maternal uniparental heterodisomy 7 associated with an SMC(7) in 36% of cells exhibited Silver–Russell syndrome 137. Anderlid et al reported on a girl with mental retardation, no obvious dysmorphisms, a de novo 47,XX,r(9)(p10p12) karyotype, and maternal uniparental heterodisomy 9 139.…”
Section: Upd Of a Whole Chromosome Associated With A Marker Or A Ringmentioning
confidence: 99%
“…The association between UPD and a supernumerary marker chromosome is very rare but at least 26 cases have been reported so far, 21 patients with maternal and four cases with paternal UPD [reviewed in Kotzot, 2002] [Bartels et al, 2003; Starke et al, 2003a,b; Wang et al, 2004; Liehr et al, 2005; Eggermann et al, 2006]. One case with paternal isodisomy of chromosome 6 was detected in a carrier of a supernumerary marker ring chromosome 6 which itself was of maternal origin [James et al, 1995].…”
Section: Introductionmentioning
confidence: 99%